IV. The Functions of Mathematical Treatment - Tinbergen, J. (The Review of Economics and Statistics, 1954)
It is certainly true to say that the present situation is unfortunate -the situation with respect to the use of mathematics in economic science -and improvement may be obtained as a consequence of a clearer understanding of the functions of mathematics. I very much welcome the attempt made by Dr. Novick, although I am inclined to put things somewhat differently. To what extent there is between us only a difference in wording and to what extent one of substance, I do not quite see. Therefore let me give my own view in my own words. The functions of mathematical treatment in economic research may perhaps best be discussed on the basis of a breakdown into various elements of a complete piece of econometric research. Not all pieces of important economic analysis are by necessity also complete: sometimes certain elements are absent, as a consequence of the special features of the problem handled. I do not want to say therefore that every contribution to economic science should show all the elements to be enumerated; but the function of mathematics becomes clearer if we consider this complete set of elements.